The Rationality Prohibition of Riba (Usury) - Sofhian, Sofhian (Institut Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2015)
Usury (henceforth called as riba) in fact has long been known and have been progressing in meaning. The study of riba was not only discussed seriously by Muslims but also other religions. If flashed back to more than two thousand years ago, the study of riba has been discussed by non-Muslims, such as Hindu, Buddhist, Jewish, Greek, Roman and Christian. In Islam, debate about riba and bank interest indicated that the problem of riba very closely related to the issue of muamalah especially those that occur in Banks and Non- Bank financial. Riba evolution concept toward interest cannot be separated from the development of the financial institutions. Therefore, this journal examine and analyze the substance of the issues of interest in a rational perspective, and at the end of this journal offers loss and profit sharing system as an alternative solution to the system of interest in transaction systems of bank and non- bank. —–Ketertarikan mengenai kajian riba senantiasa menjadi diskusi yang tidak mengalami kejenuhan, dan bahkan masih sangat hangat didiskusikan dalam ilmu ekonomi dalam Islam. Hal ini terlihat dari pembahasan mengenai riba yang senantiasa memberi warna dalam diskursus pemikiran umat Islam dan perdebatannya hampir tidak menemukan titik temu. Perdebatan pemikiran mengenai riba dan bunga bank menunjukkan bahwa persoalan riba sebenarnya sangat terkait erat dengan persoalan muamalah khususnya yang terjadi pada lembaga-lembaga keuangan Bank dan Non Bank. Evolusi konsep riba ke bunga tidak lepas dari perkembangan lembaga-lembaga keuangan tersebut. Oleh karena itu, jurnal ini mencermati dan menganalisis secara subtansi tentang persoalan riba dalam perspektif rasional, dan di akhir tulisan ini menawarkan sistem loss and profi sharing sebagai solusi alternatif pengganti sistem bunga dalam sistem transaksi pada lembaga keuangan bank dan non bank